Draft genome sequence of Burkholderia cordobensis type strain LMG 27620, isolated from agricultural soils in Argentina - Draghi, Walter Omar (2015)
Bacteria of the genus Burkholderia are commonly found in diverse ecological niches in nature. We report here the draft genome sequence of Burkholderia cordobensis type strain LMG 27620, isolated from agricultural soil in Córdoba, Argentina. This strain harbors several genes involved in chitin utilization and phenol degradation, which make it an interesting candidate for biocontrol purposes and xenobiotic degradation in polluted environments.